2015
DOI: 10.4172/2332-0702.1000171
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Perception in Institutionalized Elderly in Brazil: Psychosocial, Physical and Pain Aspects

Abstract: Objective: Identify self-rated oral health dimensions of institutionalized elderly in Brazil using the Geriatric Oral Health Assessment Index (GOHAI), and seek associations with objective, subjective and behavioral conditions. Methodology: Cross-sectional study based on a census of institutionalized elderly. A total of 1192 individuals, living in 36 long-stay institutions for the elderly (LSIE) were evaluated. Of these, 587 (49.2%) responded to the GOHAI. A questionnaire containing subjective and oral health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
4
2
0
Order By: Relevance
“…43,44 The results of the present study con rmed the signi cant negative correlation between geriatric oral health assessment index scores and brief oral health status examination scores among institutionalized elders. The results come in a line with 53 who found that self-perception is predominantly positive, which is opposite to the actual ndings of oral health, which is predominantly poor. The paradox between the clinical reality and self-perception of oral health measured in these studies, shows that reported self-perception is not enough to predict and identify oral health condition in the study population.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…43,44 The results of the present study con rmed the signi cant negative correlation between geriatric oral health assessment index scores and brief oral health status examination scores among institutionalized elders. The results come in a line with 53 who found that self-perception is predominantly positive, which is opposite to the actual ndings of oral health, which is predominantly poor. The paradox between the clinical reality and self-perception of oral health measured in these studies, shows that reported self-perception is not enough to predict and identify oral health condition in the study population.…”
Section: Discussionsupporting
confidence: 84%
“…This result doesn't agree with Doris S. et al, 2008 24 who reported that about half of the Chinese residents (51%) had a low GOHAI score whereas one-third (36%) had moderate GOHAI score and (13%) reported high GOHAI score. While, the present results come in a line with Cornejo et al,2013 42 ,Rekhi et al,2018 41 , So-Jung et al .,201953 and Silva et al,202054 who reported a signi cant poor GOHAI scores in Spanish, Indian ,Korean and Brazilian institutionalized elders respectively.The comparison between different GOHAI scores between male and female exhibited no statistically signi cant difference of the Oral health related quality of life in both genders. This result parallel to the result of study done by Azogui-Levy et al,201855 .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…43,44 The results of the present study con rmed the signi cant negative correlation between geriatric oral health assessment index scores and brief oral health status examination scores among institutionalized elders. The results come in a line with 53 who found that self-perception is predominantly positive, which is opposite to the actual ndings of oral health, which is predominantly poor. The paradox between the clinical reality and self-perception of oral health measured in these studies, shows that reported selfperception is not enough to predict and identify oral health condition in the study population.…”
Section: Discussionsupporting
confidence: 84%
“…The paradox between the clinical reality and self-perception of oral health measured in these studies, shows that reported selfperception is not enough to predict and identify oral health condition in the study population. 52 and oral health problems are considered secondary to other physical, psychological and social problems 70 .…”
Section: Discussionmentioning
confidence: 99%